The Employment Effects of Job Creation Schemes in Germany : A Microeconometric Evaluation - Marco Caliendo; Reinhard Hujer; Stephan L. Thomsen (Institute for the Study of Labor (IZA), 2005)
In this paper we evaluate the employment effects of job creation schemes on the participating individuals in Germany. Job creation schemes are a major element of active labour market policy in Germany and are targeted at long-term unemployed and other hard-to-place individuals. Access to very informative administrative data of the Federal Employment Agency justifies the application of a matching estimator and allows to account for individual (group-specific) and regional effect heterogeneity. We extend previous studies in four directions. First, we are able to evaluate the effects on regular (unsubsidised) employment. Second, we observe the outcome of participants and non-participants for nearly three years after programme start and can therefore analyse mid- and long-term effects. Third, we test the sensitivity of the results with respect to various decisions which have to be made during implementation of the matching estimator, e.g. choosing the matching algorithm or estimating the propensity score. Finally, we check if a possible occurrence of 'unobserved heterogeneity' distorts our interpretation. The overall results are rather discouraging, since the employment effects are negative or insignificant for most of the analysed groups. One notable exception are long-term unemployed individuals who benefit from participation. Hence, one policy implication is to address programmes to this problem group more tightly.
Keywords: H43; C13; J68; 330; evaluation; matching; sensitivity analysis; job creation schemes; long-term unemployed; Arbeitsbeschaffung; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Langzeitarbeitslosigkeit; Berufliche Integration; Schätzung; Deutschland